Hey everyone!(adsbygoogle = window.adsbygoogle || []).push({});

This question came up in my analysis assignment, we're studying continuity and differentiability at the moment so I'm unsure of my answer! It seems too short :( 1. Let [itex]x \in (0, \infty)[/itex]

a) Prove that [itex](x^{\frac{1}{n}})^m = (x^{\frac{1}{q}})^p [/itex] for all [itex]m,p \in \mathbb{Z} [/itex] such that [itex]mq = np[/itex]

Because of the previous we can define [itex]x^r \in \mathbb{R}[/itex] for all [itex]r \in \mathbb{Q}[/itex] by [itex]x^r = (x^{\frac{1}{n}})^m[/itex] if [itex]r = \frac{m}{n}[/itex] with [itex]m \in \mathbb{Z}[/itex] and [iitex]n \in \mathbb{N}[/itex]

b) Prove that [itex]x^{r+s} = {x^r}{x^s}[/itex] and [itex](x^r)^s = x^{rs}[/itex] for all [itex]r,s \in \mathbb{Q}[/itex]

For a), it seems to follow immediately,

If [itex]mq = np[/itex] then [itex]m = \frac{np}{q}[/itex] and so we have

[itex](x^{\frac{1}{n}})^m = (x^{\frac{1}{n}})^{\frac{np}{q}} = ((x^{\frac{1}{n}})^n)^{\frac{p}{q}} = (x^{\frac{p}{q}}) = x^{\frac{1}{n}} = (x^{\frac{1}{q}})^p[/itex] as required.

And b) is similar (there are too many exponents to latexify before my stuff gets stolen upstairs in the study floors).

I went about it proving if [itex]a \in \mathbb{R}[/itex] and [itex]m,n \in \mathbb{N}[/itex] then [itex]a^{m+n} = {a^m}{a^n}[/itex] and [itex](a^m)^n = a^{mn}[/itex] by induction. (Can you use induction over m and n by doing it twice fixing m the first time and inducting over n and the second time fixing n?).

Or it's probably better to first prove, if [itex]m\in \mathbb{Z}, n \in \mathbb{N}, x \in (0,\infty)[/itex] then [itex]x^{\frac{m}{n}} = (x^m)^{\frac{1}{n}}[/itex].

If [itex]x \in (0,\infty)[/itex] and [itex]m,n \in \mathbb{Z}[/itex] then [itex](x^m)^n = x^{mn} = (x^n)^m[/itex]. Now let [itex] y:=x^{\frac{m}{n}} = (x^{\frac{1}{n}})^m > 0[/itex]. So [itex]y^n = ((x^{\frac{1}{n}})^m)^n = ((x^{\frac{1}{n}})^n)^m = x^m[/itex]. Therefore it follows that [itex]y = (x^m)^{\frac{1}{n}}[/itex].

If we proved it for the naturals, how can we prove it for the rationals? It seems to follow naturally.

These analysis proofs seem so empty, although subtle. I have huge trouble sponging it all together into a valid proof.

Thanks a lot!

-Gareth

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Analysis - Powers of real numbers

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**